Role of Titin Missense Variants in Dilated Cardiomyopathy. Issue 11 (13th November 2015) - Begay, Rene L.; Graw, Sharon; Sinagra, Gianfranco; Merlo, Marco; Slavov, Dobromir; Gowan, Katherine; Jones, Kenneth L.; Barbati, Giulia; Spezzacatene, Anita; Brun, Francesca; Di Lenarda, Andrea; Smith, John E.; et al.
Abstract : Background: The titin gene ( TTN ) encodes the largest human protein, which plays a central role in sarcomere organization and passive myocyte stiffness. TTN truncating mutations cause dilated cardiomyopathy (DCM); however, the role of TTN missense variants in DCM has been difficult to elucidate because of the presence of background TTN variation. Methods and Results: A cohort of 147 DCM index subjects underwent DNA sequencing for 313 TTN exons covering the N2B and N2BA cardiac isoforms of TTN . Of the 348 missense variants, we identified 44 "severe" rare variants by using a bioinformatic filtering process in 37 probands. Of these, 5 probands were double heterozygotes (additional variant in another DCM gene) and 7 were compound heterozygotes (2 TTN "severe" variants). Segregation analysis allowed the classification of the "severe" variants into 5 "likely" (cosegregating), 5 "unlikely" (noncosegregating), and 34 "possibly" (where family structure precluded segregation analysis) disease‐causing variants. Patients with DCM carrying "likely" or "possibly" pathogenic TTN "severe" variants did not show a different outcome compared with "unlikely" and noncarriers of a "severe" TTN variant. However, the "likely" and "possibly" disease‐causing variants were overrepresented in the C‐zone of the A‐band region of the sarcomere. Conclusions: TTN missense variants are common and present a challenge for bioinformatic classification, especially when informative families are not available. Although DCM patients carrying bioinformatically "severe" TTN variants do not appear to have a worse clinical course than noncarriers, the nonrandom distribution of "likely" and "possibly" disease‐causing variants suggests a potential biological role for some TTN missense variants.